Control of epithelial cell migration and invasion by the IKKβ- and CK1α-mediated degradation of RAPGEF2 - Magliozzi, R; Low, T; Weijts, B; Cheng, T; Spanjaard, E; Mohammed, S; vanVeen, A; Ovaa, H; deRooij, J; Zwartkruis, F; Bos, J; deBruin, A; et al. (2013)
Epithelial cell migration is crucial for the development and regeneration of epithelial tissues. Aberrant regulation of epithelial cell migration has a major role in pathological processes such as the development of cancer metastasis and tissue fibrosis. Here, we report that in response to factors that promote cell motility, the Rap guanine exchange factor RAPGEF2 is rapidly phosphorylated by I-kappa-B-kinase-β and casein kinase-1α and consequently degraded by the proteasome via the SCFβTrCP ubiquitin ligase. Failure to degrade RAPGEF2 in epithelial cells results in sustained activity of Rap1 and inhibition of cell migration induced by HGF, a potent metastatic factor. Furthermore, expression of a degradation-resistant RAPGEF2 mutant greatly suppresses dissemination and metastasis of human breast cancer cells. These findings reveal a molecular mechanism regulating migration and invasion of epithelial cells and establish a key direct link between IKKβ and cell motility controlled by Rap-integrinsignaling. © 2013 Elsevier Inc.